Examining the Relationship Between Beliefs About Mind-Set, Beliefs About Knowledge, and Cultural Proficiency Development for K-12 Public School Teachers. Issue 2 (February 2020) - Spiess, Joseph F.; Cooper, Robyn
As the 4-year high school graduation rate of African American and Latino/a students in U.S. public schools continues to lag behind their White peers, cultural proficiency development has become an increasingly significant focus of school districts. While substantial resources have been committed in school districts across the country to improve professional development and hiring practices, measurable gains have ranged from inconsistent to negligible. Given the improved understanding of the importance of cultural proficiency development for K-12 public school teachers, developing more effective ways to predict and support cultural proficiency development is a necessary step to take in efforts to improve outcomes for all students. In this study, we used a hierarchical regression analysis to determine the extent to which mind-set and beliefs about knowledge predicted cultural proficiency. Participants were 853 K-12 public school educators. In addition to demographic variables, five constructs were identified via factor analysis—mind-set of self, mind-set of others, simple knowledge, certain knowledge, and source of knowledge. Results indicated all five constructs, including the demographic variables of gender and age, were statistically significant predictors of cultural proficiency. Implications for professional development and human resource practices are discussed as well as topics for future research.